2022
DOI: 10.1038/s41598-022-08741-9
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord microstructural changes are connected with the aberrant sensorimotor cortical oscillatory activity in adults with cerebral palsy

Abstract: Previous animal models have illustrated that reduced cortical activity in the developing brain has cascading activity-dependent effects on the microstructural organization of the spinal cord. A limited number of studies have attempted to translate these findings to humans with cerebral palsy (CP). Essentially, the aberrations in sensorimotor cortical activity in those with CP could have an adverse effect on the spinal cord microstructure. To investigate this knowledge gap, we utilized magnetoencephalographic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 85 publications
2
8
0
Order By: Relevance
“…While we did not observe any motor performance differences between groups, numerous past studies have shown that the amplitude of the β‐ERD response is closely related to motor performance (Kurz et al, 2014, 2020; Spooner et al, 2021; Wiesman et al, 2020; Wilson, Fleischer, et al, 2011). Additionally, studies have shown that patients with Parkinson's disease, as well as cerebral palsy, exhibit weakened β‐ERD responses (Heinrichs‐Graham, Wilson, et al, 2014; Trevarrow et al, 2022). The strength of such beta oscillations is at least partially driven by activity in γ‐aminobutyric acid (GABA) interneurons, with MEG studies linking increased sensorimotor cortex GABA concentration with stronger β‐ERDs (Hall et al, 2011; Muthukumaraswamy et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…While we did not observe any motor performance differences between groups, numerous past studies have shown that the amplitude of the β‐ERD response is closely related to motor performance (Kurz et al, 2014, 2020; Spooner et al, 2021; Wiesman et al, 2020; Wilson, Fleischer, et al, 2011). Additionally, studies have shown that patients with Parkinson's disease, as well as cerebral palsy, exhibit weakened β‐ERD responses (Heinrichs‐Graham, Wilson, et al, 2014; Trevarrow et al, 2022). The strength of such beta oscillations is at least partially driven by activity in γ‐aminobutyric acid (GABA) interneurons, with MEG studies linking increased sensorimotor cortex GABA concentration with stronger β‐ERDs (Hall et al, 2011; Muthukumaraswamy et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The somatosensory system is not only responsible for afferent input information but also actively communicates with the motor cortex during movement [ 68 ]. Poor sensory feedback may cause major problems with sensorimotor integration and reduce the accuracy of feedforward predictions[ 69 ]. The afferent sensory feedback could be applied to evaluate movement outcome, possibly impacting the following processing speed.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the results might convey that there are fewer motoneurons available for recruitment with contraction in adults with CP. Recent structural neuroimaging studies have shown that the cervical gray matter cross-sectional area is reduced in adults with CP and this reduction is connected to both the aberrant sensorimotor cortical activity in this population and the overall level of hand motor impairment ( 20 , 21 ). Thus, it is very plausible that the reduced FCR H-reflex excitability might reflect the changes in the size of the motor pools and/or interneurons that compose the gray matter at the cervical levels.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of possible spinal motor neuron loss has also been reported based on the decreased number of motor units found in ulnar hand muscles of adults with CP ( 19 ). More recently, a structural MR imaging study of the cervical spinal cord in adults with CP uncovered anatomical reductions in the amount of spinal cord gray and white matter ( 20 , 21 ). Furthermore, a reduction in the spinal cord cross-sectional area was found to be linked with the extent of the upper extremity impairment.…”
Section: Introductionmentioning
confidence: 99%